Arnheim's Gestalt Theory of Visual Balance: Examining the Compositional Structure of Art Photographs and Abstract Images - I C McManus; Katharina Stöver; Do Kim (i-Perception, 2011)
In Art and Visual Perception , Rudolf Arnheim, following on from Denman Ross's A Theory of Pure Design , proposed a Gestalt theory of visual composition. The current paper assesses a physicalist interpretation of Arnheim's theory, calculating an image's centre of mass (CoM). Three types of data are used: a large, representative collection of art photographs of recognised quality; croppings by experts and non-experts of photographs; and Ross and Arnheim's procedure of placing a frame around objects such as Arnheim's two black disks. Compared with control images, the CoM of art photographs was closer to an axis (horizontal, vertical, or diagonal), as was the case for photographic croppings. However, stronger, within-image, paired comparison studies, comparing art photographs with the CoM moved on or off an axis (the “gamma-ramp study”), or comparing adjacent croppings on or off an axis (the “spider-web study”), showed no support for the Arnheim-Ross theory. Finally, studies moving a frame around two disks, of different size, greyness, or background, did not support Arnheim's Gestalt theory. Although the detailed results did not support the Arnheim-Ross theory, several significant results were found which clearly require explanation by any adequate theory of the aesthetics of visual composition.